Faktor-Faktor yang Berhubungan dengan Infertilitas Primer pada Pasangan Usia Subur di Puskesmas Molibagu - Mentari Hasanuddin; Rizky Nikmathul Husna Ali; Fatmah Zakaria; Sri Mulyaningsih; Efri Leny Rauf (Pusat Kajian dan Pengelola Jurnal FKM UMI, 2025)
Primary infertility is the inability of a fertile couple to conceive after one year of regular sexual intercourse without contraception. Various factors are suspected to be associated with primary infertility, including nutritional status, menstrual cycle regularity, and cigarette smoke exposure. This study aimed to analyze the relationship between Body Mass Index (BMI),menstrual cycle, and cigarette smoke exposure with primary infertility in fertile couples at the Molibagu Community Health Center. This study used an observational analytical design with a cross-sectional approach. Sampling was conducted using purposive sampling, with 92 respondents. The research instruments were structured using questionnaires and anthropometric measurements, with data analysis using the chi-square test and logistic regression. Based on the results, it was found that the majority of respondents (52 respondents) had an overweight BMI (56,5%) 48 respondents (52,5%) had irregular menstrual cycles, 52 respondent (56,5 %) were exposed to cigarette smoke, and 55 respondents (59,8 %) experienced primary infertility.The statistical test result showed a P-Value of 0.000 < 0.05, indicating a significant relationship between body mass index (BMI), menstrual cycle, and cigarette smoke exposure and the incidence of primary infertility in couples of childbearing age.